PANRESISTANT SUPERBUGS: ARE WE AT THE EDGE OF A ‘MICROBIAL HOLOCAUST’ - Khan, I. D.; Rajmohan, K. S.; Jindal, A. K.; Gupta, R. M.; Khan, S.; Shukla, M.; Singh, S.; Mustafa, Sh.; Tejus, A.; Narayanan, S. (International Journal of Medicine and Medical Research, 2017)
Contemporary healthcare has progressed towards world health security through advancements in medication-based and surgical interventions, supported by the success of antimicrobial therapy. The emergence of panresistant infectious diseases is becoming a public health problem worldwide. Panresistance is attributable to a complex interplay of antimicrobial overuse in healthcare facilities due to lack of regulatory commitment in the backdrop of natural mutations in pathogens and rise in immunocompromised hosts. Developing countries are facing the brunt in epidemic proportions due to strained public health infrastructure and limited resource allocation to healthcare. Panresistance is a biological, behavioural, technical, economic, regulatory and educational problem of global concern and combating it will require concerted efforts to preserve the efficacy of the available antimicrobials. An intensified commitment needs to be taken up on a war footing to increase awareness in the society, increase laboratory capacity, facilitate antimicrobial research, foster emphasis on infection control and antimicrobial stewardship, and legislation on manufacturing, marketing and dispensing of antimicrobials.